RHYMES OF INDONESIAN CREATIVE TRANSLATION IN SLOGANS - Raden Roro Shinta Felisia (Jurnal Sosial Humaniora dan Pendidikan, 2023)
The language of advertising, including slogans, may use rhyme, the phonological device which aims to ease the audience to remember the advertising. Considering a slogan should be fully translated into other languages, the researcher finds the importance of describing a slogan translation, especially those using rhyme. They are called creative translation, one of the translation strategies in advertising. Seven (7) rhymes of Indonesian creative translation are in five (5) slogans. In frequency, two (2) slogans have two (2) rhymes respectively. The other three (3) slogans have one (1) rhyme respectively. In the sound of rhyme, there are two (2) vocal letters, one (1) partial syllable, and four (4) syllables. In terms of the rhyme-used units (such as word and phrase), there are seven (7) types of units for those seven (7) rhymes. Based on the result regarding rhyme-used units, there are various possibilities a translator can apply since using rhyme relates to a translator’s creativity to provide charm.